Family planning practices amongst women of reproductive age groups in field practice area of rural health training centre of Government Medical College, Miraj, Maharashtra - Kshirsagar, Vikas; Rajderkar, Shekhar; Dudhbhate, Birudev (International Journal Of Community Medicine And Public Health, 2018)
Background: Family planning services have the potential to improve the quality of the lives of people. Family planning deals with reproductive health of mother, having adequate birth spacing, avoiding undesired pregnancies and abortions, preventing sexually transmitted diseases and improving the quality of life of mother, fetus and family as a whole. This study was conducted in the field practice area to learn about various family planning practices and reasons for non-use. Methods: A cross-sectional study was carried out amongst women of reproductive age group in the field practice area of Rural Health Training Centre of Dept. of Community Medicine of a Government Medical College, Miraj Dist- Sangli, Maharashtra during the period of January to March 2018. Total of 2964 eligible couples were interviewed by the trained staff using the pre-tested questionnaire. Data was analyzed by using appropriate test whenever necessary. Results: The contraceptive prevalence was found to be 80.8%. Majority 92.8% couples who had two children were using one of the contraceptive methods. Among 2396 contraceptive users, 76% of couples had followed permanent method of sterilization. The permanent method opted by majority of couples was female sterilization i.e. 75.8%, whereas male sterilization was carried out by only 0.2% partners. Among the couples who were using temporary methods, majority partners were using Nirodh. Conclusions: Promotion of contraceptive usage should be done through intense awareness campaigns and continuous motivation should be carried in the current contraceptive users.